A sustainable approach for smallholder farmers: evaluation of plant by-products and industrial waste in wheat cultivation - Muhammet Cagri Oguz (PeerJ, 2025)
Large amounts of waste and by-products are generated during the extraction of essential oils, leading to disposal challenges. Integrating these by-products into the production systems of smallholder farmers may help reduce yield losses caused by environmental stress factors. This study investigated the potential use of plant waste and by-products from aromatic plants as bioregulators in wheat cultivation. Greenhouse and field experiments were conducted to evaluate the effects of these materials on yield parameters and biochemical markers in wheat. The treatments included: T0 (control), T1 (plant extract), T2 (plant biomass), and T3 (plant extract + plant biomass). In the greenhouse experiment, the T3 treatment advanced the onset of tillering by 5.4 days, stem elongation by 5.6 days, and heading by 12 days compared to the control. In the field experiment, T3 reduced the heading onset by an average of 5.27 days relative to the control. Additionally, the highest yield was recorded in the T3 treatment, reaching 264.96 kg da−1. These findings suggest that by-products from aromatic and medicinal plants can serve as cost-effective, sustainable, and environmentally friendly biostimulants to enhance yield in agricultural production.